Facial orthopedics - Linden, Frans P. G. M. van der, 1932-; Quintessence Publishing Co.; Dentaurum (Firm) (Berlin : Quintessence Pub. Group ; Ispringen, Germany : Dentaurum, 2005)
'Methods of influencing facial growth through facial orthopedics are demonstrated, including explanations of their modes of action and their long-term effects. Facial orthopedics has the potential to improve functional conditions, promote a more favorable jaw relationship, guide the development of the dentition, and improve the position of malaligned teeth. Multiple clinical examples, including several short video clips, demonstrate how and when to treat as well as the outcome of various facial-orthopedic procedures. All of the written and spoken text can be reproduced in six different languages (English, German, Spanish, French, Italian, Portuguese).'--Publisher description from website.
Title from disc label
System requirements: Pentium-class processor with 500 MHz; 256 MB RAM; Windows 2000/XP; video card supporting 1024x768 pixels at 16 bit (high) colour; DVD-ROM drive; 50 MB free hard disk space.
Includes complete text and soundtrack in English, Spanish, French, German, Italian, and Portuguese
Keywords: Facial Bones -- surgery; Jaw -- surgery; Orthodontics, Corrective -- methods